Synthesis, characterization and antimicrobial activity of cobalt and cobalt sulphide nanoparticles against selected microbes that are found in wastewater - Phuti, Moukangoe Getrude (Vaal University of Technology, 2018)
Water shortages, water pollution and climate changes are highly interrelated global issues. These have raised immense concerns about serious adverse effects on the quality, treatment and re-use of wastewater. A major role of water is for vitality of life on earth. Water is recognized as source of evolution from origin to degree of civilization, since it is an essential resource its treatment becomes a necessity for day to day for life. Nanoparticles and their application in treatment of wastewater is becoming a major area of research. It is mainly applicable to the removal of major contaminants like microorganisms. This study was carried out with an objective to investigate the antibacterial and antifungal potentials of nanoparticles. Cobalt and cobalt complexes of urea and thiourea were synthesized and characterized using UV-Vs, PL, FTIR, TEM, SEM, XRD and TGA techniques. The Co particles are in a mixture of rod, agglomerates with irregular shape around 50 – 100 nm in diameter. The Co/Thiourea particles appear to be around 10 – 30nm in size. The Co complexed with urea images showed spherical to hexagonal shape with 50 nm size in diameter. The antimicrobial activity was determined using Minimum Inhibitory and bactericidal concentration and the well diffusion method. The antibacterial and antifungal activities of ratios (1:1, 1:2, 1:3, 2:1 μg/mL) of doped cobalt nanoparticles were tested against a panel of five Gramnegative bacteria - (Escherichia coli, Pseudomonas aeruginosa, Shigella enterica, Salmonella typhi and Salmonella sonnei) human pathogenic bacteria; and two fungal strains - Aspergillus niger and Candida albicans. Zones of inhibition as a consequence of nanoparticles were compared with that of different standards like Neomycin for antibacterial activity and Amphotericin B for antifungal activity. The results showed a remarkable inhibition of the bacterial growth against the tested organisms. The most striking feature of this study is that Cobalt, Urea and Thiourea nanoparticles have antifungal activity comparable or more effective (as in case of Thiourea on A. niger) than Amphotericin B and nearly promising antibacterial activity although not comparable to Neomycin.
M. Tech. (Department of Biotechnology, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Nanoparticles, Co, Co/Tu, Co/U, MIC; Pseudomonas aeruginosa; Shigella enterica; Escherichia coli; Salmonella sonnei; Salmonella typhi; Candida albicans; Aspergillus niger; Anti-infective agents.; Nanoparticles.; Cobalt.; Sewage -- Purification.; Dissertations, Academic -- South Africa.